Transport Modulation Through Electronegativity Gating in Multiple Nitrogenous Circuits. Issue 20 (15th April 2022) - Duan, Ping; Wang, Yaping; Chen, Lichuan; Qu, Kai; Liu, Junyang; Zhang, Qian‐Chong; Chen, Zhong‐Ning; Hong, Wenjing
Abstract: Investigating the correlations of electron transport between multiple channels shows vital promises for the design of molecule‐scale circuits with logic operations. To control the electron transport through multiple channels, the modulation of electronegativity shows an effective frontier orbit control method with high universality to explore the interactions between transport channels. Here, two series of compounds with a single nitrogenous conductive channel (Sg) and dual‐channels (Db) are designed to explore the influence of electronegativity on electron tunneling transport. Single‐molecule conductance measured via the scanning tunneling microscope break junction technique (STM‐BJ) reveals that the conductance of Db series is significantly suppressed as the electronegativity of nitrogen becomes negative, while the suppression on Sg is less obvious. Theoretical calculations confirm that the effect of electronegativity extends to a dispersive range of molecular frameworks owing to the delocalized orbital distribution from the dual‐channel structure, resulting in a more significant conductance suppression effect than that on the single‐channel. This study provides the experimental and theoretical potentials of electronegativity gating for molecular circuits. Abstract : The modulation of the electron transport in multiple conducting channels influenced by the electronegativity variation is evaluated by electronegativity tuning on single‐ (Sg series) and dual‐channel (Db series) nitrogenous compounds. This work explores the electron transport mechanism in nitrogenous molecules with different channels and electronegativity, paving the way for designing integrated molecular devices for electronics and nanotechnology.